ANALISIS LAPORAN KEUANGAN SEBAGAI ALAT PENILAIAN KINERJA KEUANGAN PADA CV. MUARA PERMAI DI PEKANBARU - Olivia Destri Monica; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research aims to determine and analyse financial performance starndards from the 2015-2019 period. This research uses secondary data in the form of data obtained by the author through statements of CV. Muara Permai in Pekanbaru required researchers to analyse liquidity, solvency, profitability and activity. The results of the analysis show that the analysis of the financial statements of CV. Muara Permai from the 2015-2019 period based on the ratio of liquidity, solvency, profitability and activity are: 1) liquidity ratio analysis, current ratio gets “Bad” predicate; 2) analysisof the solvency ratio, debt to total assets ratio got the”Very Good”predicate, and debt to equity ratio got the “ Very Good” predicate; 3) analysis of profitability ratios, return on assets received the predicate “Bad”, return on equity received the predicate “Bad”, gross profit margin received the predicate “Very Good”, and net profit margin received the predicate “Not Good”; 4) analysis of activity ratios, total assets turnover received the predicate “Not Good”, and working capital turnover received the predicate “Good”.   Keywords: Financial Performance, Liquidity, Solvency and Activity.